A Study on Hypothyroidism in a School for the Mentally Retarded in Bandung - J. Asikin; S. Dibjosubroto; A.H. Pallencaoe; L.F. Luhulima (Indonesian Pediatric Society, 1978)
A study was made on 114 pupils from a school for the mentally retarded in Bandung. In 50 subjects the length ratio between the upper and the lower segment of the body were more than one; of 44 subjects (32 debils, 11 imbecils, 1 borderline debil-imbecil) we found 2 with hypertelorism, 1 with dry and rough skin, and 1 with gross and fine motor abnormalities. Dental development and bone ages were within normal limits. No rise in serum cholesterol and changes in NTR (Normalized Thyroxine Ratio) were found. T4 (thyroxine) values were within normal limits. Radioactive iodine uptake and scanning of 42 subjects showed hyperplasia in 32 and euthyroidism in 5 subjects. Three subjects suggested a possible iodine contamination, 2 subjects with uptake of more than 50%, one of them showed adenoma (toxic?) on scanning; on the other one scanning was not done. Hypothyroidism was not found; 32 subjects which showed hyperplasia were suggestive of active thyroid. Further studies should be done in another sample of population to trace the problems of hypothyroidism in childhood.